Lower limb muscle lengths in rowing a preliminary study - Retailleau, M.; Domalain, M.; Ménard, M.; Colloud, F. (ISBS Proceedings Archive (Michigan), 2017)
This study aimed to characterise the lower limb muscular coordination in rowing. A musculoskeletal model was developed to be used for movements exhibiting large joints range of motion. Maximum static muscle lengths computed from five static stretching tests were compared with muscle lengths extracted while rowing. Muscle lengths were derived from lower limb kinematics collected using a motion analysis system. Our results showed that classical stretching tests were suitable for a muscle group but must be more specific to target isolated muscle. During rowing trials, bi-articular muscle patterns were subject-dependant with hamstring lengths close to their maximum lengths. Asymmetries were observed for few muscles. Further studies are necessary to confirm these promising findings that may maximise rowing performance and minimise rowing injuries.